PROCEDURAL DEVIATIONS AND STATE LOSSES IN THE ABUSE OF AUTHORITY IN THE 2015 SUGAR IMPORT POLICY - Izmy Savira; Krisnadi Nasution (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The sugar import policy issued by the Minister of Trade in 2015 generated significant controversy because it was deemed to contradict existing legal provisions, was carried out without proper inter-ministerial coordination, and posed a potential risk of state financial loss. Although government data indicated a national sugar surplus, import permits were still granted to private entities. This situation raised suspicions of abuse of authority and prompted judicial review through court proceedings. This study aims to examine the legal framework governing sugar importation within the national regulatory system and to analyze the application of the concept of abuse of authority in the Minister of Trade’s discretionary policy, as assessed in Decision Number 34/Pid.Sus-TPK/2025/PN Jkt.Pst. The research employs a normative juridical method using statutory and conceptual approaches. Primary legal materials include laws related to trade, food, customs, sugar import regulations, and the relevant court decision. The data were gathered through library research, while analysis was conducted through normative interpretation, legal reasoning, and examination of factual findings contained in the judgment. The research demonstrates that although the regulatory structure governing sugar imports is comprehensive, its implementation in this case deviated from established procedures. The Minister of Trade issued a permit for the importation of 105,000 tons of raw crystal sugar without conducting the required inter-ministerial coordination meeting or technical verification. The court found that the policy constituted an abuse of office for the benefit of specific parties, resulting in state losses estimated at approximately Rp400 billion. In its considerations, the panel of judges concluded that the actions fulfilled the elements of abuse of authority and violated principles of good governance. The study concludes that discretionary power cannot be exercised arbitrarily, as it must meet cumulative requirements set out in the Administrative Governance Act. The 2015 sugar import policy is proven to be inconsistent with applicable legal standards and contains elements of abuse of authority. The study suggests several implications, including strengthening oversight mechanisms, standardizing technical verification procedures, integrating cross-ministerial data systems, and enforcing strict sanctions to prevent corruption in strategic trade policies.